Efficacy of tildrakizumab for moderate‐to‐severe plaque psoriasis: pooled analysis of three randomized controlled trials at weeks 12 and 28. (5th March 2019) - Papp, K.A.; Reich, K.; Blauvelt, A.; Kimball, A.B.; Gooderham, M.; Tyring, S.K.; Sinclair, R.; Thaci, D.; Li, Q.; Cichanowitz, N.; Green, S.; La Rosa, C.
Abstract: Background: Efficacy of tildrakizumab for plaque psoriasis was demonstrated in randomized, placebo‐controlled trials. Objective: To consolidate tildrakizumab efficacy results by pooling data. Methods: Data ( N = 2081) from tildrakizumab 100 mg, tildrakizumab 200 mg and placebo groups in three trials were pooled. Results: Proportions of Psoriasis Area and Severity Index (PASI) 75 responders at week 12 were better with tildrakizumab 100 mg (62.3%) and tildrakizumab 200 mg (64.8%) vs. placebo (5.6%; P < 0.0001) and for PASI 90, PASI 100 and Physician's Global Assessment (PGA) 'clear' or 'minimal' vs. placebo ( P < 0.0001). Responses increased from weeks 12 to 28. Week 12 PASI and PGA responses to tildrakizumab vs. placebo were numerically greater in patients with lower vs. higher bodyweight and were better with tildrakizumab 200 mg than tildrakizumab 100 mg for patients with higher bodyweight. Week 12 PASI 75 responses vs. placebo with tildrakizumab 100 mg were similar between patients with (55.0%) or without (56.7%) prior biologics. PASI 90, PASI 100 and PGA responses were generally higher in patients without prior biologics. Week 8 PASI 50 response predicted PASI 90 response. Conclusion: Pooled data confirmed the efficacy of tildrakizumab for moderate‐to‐severe plaque psoriasis.